Incidental Durotomy in Lumbar Spine Surgery: Incidence, Risk Factors And Management - Mohamed Nosseir (Egyptian Spine Association, 2014)
Background Data: Incidental durotomy is a common complication of lumbar spine operations for degenerative disorders. Its incidence changes depending on a few risk factors. Purpose: Our study aims to estimate the incidence of unintentional durotomy during operations for degenerative lumbar spinal disorders, risk factors as well as the intraoperative and postoperative management of this complication. Patient Sample: Over a 3 years period from January 2011 and December 2013, 630 patients were operated on for degenerative lumbar disorders in our department of neurosurgery. They were clinically followed up for about 24 months. Method: The surgical approaches for primary operations included uni-lateral fenestration, bi-lateral fenestration, hemilaminectomy and laminectomy. The surgeries were performed by different neurosurgeons with different professional degree and operative experience. For patients with canal stenosis, the surgical approaches included bi-lateral fenestration and laminectomy. With regards to recurrent cases, we remove the compressive element, whether it is the epidural scar or the disc fragment. Results: During the study period, 432 patients (68.6%) were operated on for lumbar disc herniation, 172 patients (27.3%) were operated on for lumbar spinal stenosis and 26 patients (4.1%) were operated on for recurrent cases. Incidental durotomy occurred in 30 cases, resulting in an overall incidence rate of 4.76%. Unintentional durotomy occurred in 10 (33.33%) of the patients with herniated disc, in 9 (30%) of thepatients with lumbar spinal stenosis and in 11 (36.67%) of the patients who were operated on for recurrences. The most common risk factors were: obesity, recurrence and the physician’s surgical experience. Intraoperative dural fissures were repaired through suture, by applying muscle or fat graft. Two CSF fistulas existed and repaired during reoperation. Conclusion: Incidental dural fissures during operations for degenerative lumbar disorders should be recognized and immediately fixed to avoid complications such as CSF fistula, osteodiscitis and increased medical costs. Preventing, identifying and managing unintentional durotomies can be optimally achieved by applying and respecting efficient surgical techniques and a standardized treatment protocol. (2014EJ067)